“BE YOURSELF” (The Creation of a Music Composition) - Asep Saepul Haris; Rahayu Supanggah; Pande Made Sukerta; Bambang Sunarto (PANGGUNG, 2017)
AbstractAn artistic workmanship is a creative work process of an artist in creating artworks. Artwork meant by the writer is "Be Yourself", which is related to the establishment of his self-characters that grown up in Sundanese culture. Life journey was a dynamic process and became the will of the Almighty. God's destiny and life journey made the writer as “urangsumando” (people related by marriage) in Minangkabau. Cross-cultural was a life journey to be (yourself) and the destiny he should do – being in two different culture positions. Such differences did not automatically make the writer soluble in integration – he existed in two conceptions. In the realization, how the concepts are able to deliver other offers which have contribution to the development of artistic creation. The discussion in this article is the artistic forms as the exploration, working material, and forms of performance.Keywords: artistic, workmanship, music work